If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 5 = -5x + 6 Reorder the terms: 5 + -4x = -5x + 6 Reorder the terms: 5 + -4x = 6 + -5x Solving 5 + -4x = 6 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 5 + -4x + 5x = 6 + -5x + 5x Combine like terms: -4x + 5x = 1x 5 + 1x = 6 + -5x + 5x Combine like terms: -5x + 5x = 0 5 + 1x = 6 + 0 5 + 1x = 6 Add '-5' to each side of the equation. 5 + -5 + 1x = 6 + -5 Combine like terms: 5 + -5 = 0 0 + 1x = 6 + -5 1x = 6 + -5 Combine like terms: 6 + -5 = 1 1x = 1 Divide each side by '1'. x = 1 Simplifying x = 1
| x+(1/2)x=24 | | 4x-4=3x-1 | | 6X-3y+2z=14 | | x/4-3y | | 5(3x-2)=15x- | | 6x-4+2x=8x-10 | | x+x+(5+-2X)=23 | | -3(-4w-2x+5)= | | 4x^3+32=-3 | | 8h+28=76+7h | | (e^5x)^5/8e^3x | | 3(x-6)+2x=5x-18 | | (e^5x)^5/e^3x | | .25[2.5x+1.5(x-4)]=-x | | (x+3)(x-5)= | | 4x^3+32=1 | | 4x-2yi=12 | | 19=7-2 | | X-y-1=4-2xi-yi | | 2x-3yi=4+9i | | 2x-3yi=4+9i | | 7x+8y=56 | | 11-(-10x)+2x-(-9)= | | 15x-283=6x-13 | | 137-5x=22x+20 | | 4x^3+3x^2-2x-1=0 | | 2g/20(g+h) | | 3x+7=3-x | | 2g/20g+h | | 5-n=2n-4 | | -8a^-7b^2c/2a^-6b^3c | | X^2+2x+56= |